Occupational therapists' ethical reasoning: Assessing student and practitioner responses to ethical dilemmas. - Kanny EM (Occupational Therapists' Ethical Reasoning: Assessing Student & Practitioner Responses to Ethical Dilemmas, 1996)
Today's complex and fast-changing healthcare environment is generating concurrent ethical dilemmas that healthcare practitioners must be able to recognize, solve, and act upon accordingly. With the increased focus on ethics in healthcare, greater attention in recent years has been given to ethics education by professional groups. Occupational therapy is a health profession confronted by these issues, however, one in which there is a paucity of studies related to ethical reasoning and education.The purpose of this study was to address the question of whether professional-level occupational therapy education or practice experience changes a person's level of ethical reasoning as measured by the Defining Issues Test (Rest, 1979) and the Occupational Therapy Dilemmas Test (Hansen, 1984). A static group comparison design was used for the purpose of establishing the effect of professional level education and practice. A proportional random sample of nine of the 71 occupational therapy programs in the United States provided access to the three subject groups: beginning students; senior-level students; and practicing therapists. Of the 948 students and therapists asked to participate in the study, 465 (49.1%) consented to do so; 397 (85.45%) completed the study instruments. There were 389 paired sets of scores usable for the study.The most salient finding of the study was that there were no statistically reliable differences in the scores of the three subject groups on either the Defining Issues Test (DIT) or the Occupational Therapy Dilemmas Test. Further, no statistically reliable relationship was found among scores on these tests and the variables of age, gender, and years of college education. Thus, the students completing their professional education did not increase their level of principled ethical reasoning.If the field of occupational therapy wishes to raise the level of principled ethical reasoning of its graduates, effective teaching methods must be developed and studied for their effectiveness. Further studies are needed to identify educational approaches that can be used by occupational therapy programs to challenge students to use higher levels of ethical reasoning.